PREVENTING MAJORITARIAN VETO IN HOUSE OF WORSHIP LICENSING: A HUMAN RIGHTS-BASED DUE PROCESS MODEL - Adhe Ismail Ananda; La Ode Dedihasriadi; Pery Rehendra Sucipta; Yeni Haerani; Arie Ekawie Baskhoro (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2026)
This article examines majoritarian veto in house-of-worship licensing in Indonesia, defined as a condition in which majority pressure or preferences de facto replace administrative legal standards in permit decisions. The problem arises from the gap between constitutional guarantees of religious freedom and worship, technical licensing rules under the 2006 Joint Ministerial Regulation, and local discretion, which is not always subject to measurable procedural safeguards. This study aims to formulate a human rights-based due process model that prevents licensing mechanisms from becoming instruments of exclusion against religious minorities. It employs normative legal research with statutory, conceptual, and case approaches, drawing on constitutional provisions, PBM 2006, academic literature, and contextual case materials, including a 2026 licensing dispute in Kupang City. Legal materials and academic literature were collected through document study and analyzed through normative harmonization, human rights testing, and procedural due process assessment. The findings identify three main vulnerabilities: community support requirements and religious harmony forum recommendations that may function as social vetoes; fragmented local procedures that may produce delay-as-denial; and public order arguments used without objective indicators. The article contributes to religious freedom and diversity governance scholarship by conceptualizing majoritarian veto as a form of procedural discrimination and proposing national minimum procedural standards, public consultation as impact mapping, documented step-by-step procedures, mandatory reason-giving, and time-bound administrative remedies. Local discretion is legitimate only when used for evidence-based technical assessment, while religious harmony must be built through procedural justice, accountability, and equal protection of constitutional rights. Abstrak Artikel ini mengkaji veto mayoritas dalam perizinan rumah ibadah di Indonesia, yang didefinisikan sebagai kondisi ketika tekanan atau preferensi mayoritas secara de facto menggantikan standar hukum administratif dalam pengambilan keputusan perizinan. Masalah ini muncul dari kesenjangan antara jaminan konstitusional atas kebebasan beragama dan beribadah, aturan perizinan teknis berdasarkan Peraturan Menteri Bersama 2006, dan diskresi lokal, yang tidak selalu tunduk pada perlindungan prosedural yang terukur. Studi ini bertujuan untuk merumuskan model proses hukum berbasis hak asasi manusia yang mencegah agar mekanisme perizinan tidak menjadi instrumen eksklusi terhadap minoritas agama. Studi ini menggunakan penelitian hukum normatif dengan pendekatan hukum, konseptual, dan kasus, yang mengacu pada ketentuan konstitusional, PBM 2006, literatur akademis, dan materi kasus kontekstual, termasuk sengketa perizinan tahun 2026 di Kota Kupang. Materi hukum dan literatur akademis dikumpulkan melalui studi dokumen dan dianalisis melalui harmonisasi normatif, pengujian hak asasi manusia, serta penilaian terhadap proses hukum secara prosedural. Temuan mengidentifikasi tiga kerentanan utama: persyaratan dukungan masyarakat dan rekomendasi forum harmoni beragama yang dapat berfungsi sebagai veto sosial; Prosedur lokal yang terfragmentasi dapat menghasilkan penundaan sebagai penolakan; dan argumen ketertiban umum yang digunakan tanpa indikator objektif. Artikel ini berkontribusi pada kajian kebebasan beragama dan tata kelola keragaman dengan mengonseptualisasikan veto mayoritas sebagai bentuk diskriminasi prosedural serta mengusulkan standar prosedural minimum nasional, konsultasi publik untuk memetakan dampaknya, prosedur langkah demi langkah yang terdokumentasi, pemberian alasan yang wajib, dan upaya hukum administratif yang terikat waktu. Diskresi lokal hanya sah bila digunakan untuk penilaian teknis berbasis bukti, sementara harmoni beragama harus dibangun melalui keadilan prosedural, akuntabilitas, dan perlindungan yang sama terhadap hak-hak konstitusional.